NON PHARMACOLOGICAL APPROACH FOR TREATMENT OF OSMF- A REVIEW (International Journal of Ayurveda and Pharma Research, 2020)
Ancient medicine used herbs, for their medicinal purposes and theraeutic benefits. Herbs became important in the global context today, because they offer solutions to the various concerns faced by mankind. Herbal extracts have been proven effective because they interact within the body with the special chemical receptors. Nevertheless as such herbal medicinal products were part of human evolutionary cycle substituted with allopathic preparations. In the last few years because of usage of antimicrobials and antifungals drugs, many organisms with apparent side have gained resistance with negative consequences. Late resurgence towards herbal medicines is therefore on the horizon rise. The following manuscript sheds light on the various organic materials possible remedies for treating oral mucosal lesions. The study is to review the non-pharmacological therapies in the management of Oral Submucous Fibrosis.